2017
DOI: 10.1007/s13197-017-2921-0
|View full text |Cite
|
Sign up to set email alerts
|

Pecan walnut (Carya illinoinensis (Wangenh.) K. Koch) oil quality and phenolic compounds as affected by microwave and conventional roasting

Abstract: In this study, the effects of conventional and microwave roasting on phenolic compounds, free acidity, peroxide value, fatty acid composition and tocopherol content of pecan walnut kernel and oil was investigated. The oil content of pecan kernels was 73.78% for microwave oven roasted at 720 W and 73.56% for conventional oven roasted at 110 °C. The highest free fatty acid content (0.50%) and the lowest peroxide value (2.48 meq O/kg) were observed during microwave roasting at 720 W. The fatty acid profiles and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Finally, in the three studied oils the main fatty acid fraction was PUFA, as previously referred (Calvo et al, 2011;Özcan 2009), and the highest contents of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) were found in organic solvent extracted oil (Calvo et al, 2011), as in pecan walnut oil (Juhaimi, Özcan, Uslu, & Doḡu, 2017). According to the loading plot, the highest values of PUFA fatty acids are observed in model 1 oil, while the highest amount of SFA are observed in model 3 oil, indicating that extracting oil with organic solvent caused a degradation of polyunsaturated fatty acids.…”
Section: Characterization Of the Walnut Oilsmentioning
confidence: 57%
See 1 more Smart Citation
“…Finally, in the three studied oils the main fatty acid fraction was PUFA, as previously referred (Calvo et al, 2011;Özcan 2009), and the highest contents of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) were found in organic solvent extracted oil (Calvo et al, 2011), as in pecan walnut oil (Juhaimi, Özcan, Uslu, & Doḡu, 2017). According to the loading plot, the highest values of PUFA fatty acids are observed in model 1 oil, while the highest amount of SFA are observed in model 3 oil, indicating that extracting oil with organic solvent caused a degradation of polyunsaturated fatty acids.…”
Section: Characterization Of the Walnut Oilsmentioning
confidence: 57%
“…The proportion of unsaturated fatty acids was significantly correlated to OSI (Table ); in fact, a significant correlation exists between OSI and MUFA ( r = −.802, p < .01), and between OSI and PUFA ( r = .784, p < .01). Apart from that, PUFA were highly correlated to TTC ( r = .768, p < .01) and γ‐tocopherol ( r = .822, p < .01), the most abundant tocopherol isomer found in walnut oil (Calvo et al, ), as in pecan walnut oil (Juhaimi, Özcan, Uslu, & Doḡu, ).…”
Section: Resultsmentioning
confidence: 99%
“…γ-Tocopherol is one of the major bioactive compounds found in pecan and pecan oil. It ranges from 21 to more than 400 mg/ kg of oil or 16.0 to 30.5 mg/100 g of kernel; although a study by Juhaimi et al (Juhaimi et al, 2017) reported values between 3,090 and 4,650 mg/kg of oil extracted from raw and roasted pecans obtained from Turkey (the cultivar was not mentioned in the paper). These authors did not detect any other tocopherol analogues in their samples and observed that microwave roasting reduced the γ-tocopherol content more than conventional oven roasting.…”
Section: Contentmentioning
confidence: 96%
“…It is apparent that the effect of the oil extraction technique or conditions on the content of oleic and linoleic acids is marginal compared with their wide natural variations in samples of different origins and cultivars. The high- Oleic acid (w-9) 56.3-72.5 % Supercritical fluids Different cultivars and extraction conditions, residual oil Alexander et al, 1997;Salvador et al, 2016 51.1-75.3 % Soxhlet with different solvents Different cultivars, locations, harvest years, tree ages, ripening stages, residual oil, raw and roasted nuts Bouali et al, 2013;Juhaimi et al, 2017;Salvador et al, 2016;Toro-Vazquez et al, 1999;Venkatachalam et al, 2007;Venkatachalam & Sathe, 2006;Wakeling et al, 2001 38.2-75.0 % RT with different solvents and extraction protocols Different cultivars, locations, harvest years, extraction conditions Derewiaka et al, 2014;Domínguez-Avila et al, 2013;Flores-Córdova et al, 2016;Miraliakbari & Shahidi, 2008b;Ryan et al, 2006;Villarreal-Lozoya et al, 2007 53.9-78.1 % Mechanical pressing Different cultivars, harvest years and extraction conditions, commercial oils from different locations Castelo-Branco et al, 2016;do Prado et al, 2013;Fernandes et al, 2017;Scapinello et al, 2017 53.0-65.3...…”
Section: Phytochemicals In Pecan Oilmentioning
confidence: 99%
See 1 more Smart Citation